IDENTIFICATION OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS USING TOUCHDOWN PCR AND PHENOTYPIC METHODS FROM PATIENTS AND HOSPITALS ENVIRONMENTS IN DIFFERENT IRAQI CITIES - Abd Zaid, A. M.; Kandala, N. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The study was aimed to evaluate the prevalence of MRSA in some Iraqi hospitals and determine the most powerful methods for identification of MRSA, in order to achieve the, 278 samples were collected from different hospitals in Iraq in various intervals, 204 out of 287 were identified as Staphylococcus aureus by conventional cultural methods and microscopic characteristics and 177 isolates are identified as MRSA by using HiCrome MeReSa Agar Base medium, but 154 of 177 (87%) isolates are methicillin resistance in sensitivity test. MRSA isolates were highly resistant to β-lactam antibiotics and considered multidrug resistant (MDR) in percent of (94.9%). Touchdown PCR used to identify the isolates, 97.05% were identified as Staphylococcus aureus, while 80.88%  as MRSA.